Classifying Anal Intraepithelial Neoplasia 2 Based on LAST Recommendations: Interobserver Agreement Among Experienced Pathologists. Issue 6 (19th November 2020) - Liu, Yuxin; McCluggage, W Glenn; Darragh, Teresa M; Zheng, Wenxin; Roberts, Jennifer M; Park, Kay J; Hui, Pei; Blakely, Morgan; Sigel, Keith; Gaisa, Michael M
Abstract: Objectives: The Lower Anogenital Squamous Terminology (LAST) recommendations classify human papillomavirus–associated squamous lesions into low- and high-grade squamous intraepithelial lesions (LSILs/HSILs). Our study aimed to assess interobserver agreement among 6 experienced pathologists in assigning 40 anal lesions previously diagnosed as anal intraepithelial neoplasia 2 (AIN 2) to either HSIL or non-HSIL categories. Methods: Agreement based on photomicrographs of H&E alone or H&E plus p16 immunohistochemistry was calculated using κ coefficients. Results: Agreement was fair based on H&E alone (κ = 0.42; 95% confidence interval [CI], 0.34-0.52). Adding p16 improved agreement to moderate (κ = 0.55; 95% CI, 0.54-0.62). On final diagnosis, 21 cases (53%) had unanimous diagnoses, and 19 (47%) were divided. When designating p16 results as positive or negative, agreement was excellent (κ = 0.92; 95% CI, 0.83-0.95). Among variables (staining location, extent, and intensity), staining of the basal/parabasal layers was a consistent feature in cases with consensus for positive results (20/20). Of the 67 H&E diagnoses with conflicting p16 results, participants modified 32 (48%), downgrading 23 HSILs and upgrading 9 non-HSILs. Conclusions: Although p16 increased interobserver agreement, disagreement remained considerable regarding intermediate lesions. p16 expression, particularly if negative, can reduce unwarranted HSIL diagnoses and unnecessary treatment.